A kinematic analysis of the hammer throw technique in elite female athletes: a comparative study between Chinese and international competitors - Liu, Weijie; Ding, Yiling; He, Ruihua; Li, Jianchen (Frontiers in Physiology, 2025)
PurposeThis study aimed to examine the kinematic features of the hammer throw technique among elite female athletes worldwide, which is essential for advancing the development of women’s hammer throw in China. By examining the technical differences between Chinese female hammer throwers and their international counterparts, this research offers data support to help Chinese athletes further refine and optimise their throwing techniques, thereby strengthening the scientific basis of training in this discipline.ResultsThe study found that the average release velocity of Chinese athletes was lower than that of world-class athletes, with Zheng Wang recording the highest release velocity among the Chinese throwers. There was minimal difference in the average release angle between Chinese and international athletes. Apart from Zheng Wang, most Chinese athletes showed irregular timing in their average rotational phases, which negatively impacted the release phase. Notably, the average preliminary swing speed of Chinese athletes was markedly higher than that of international athletes, indicating a technical tendency towards active acceleration during the initial rotation phase. Additionally, the average trajectory length per turn among top Chinese athletes was generally longer than that of elite international athletes.ConclusionThe international elite female hammer throwers exhibit superior release-related indices and more effective double-support mechanics compared with their Chinese counterparts. These results highlight the central role of double-support coordination, trunk–pelvis coupling, and phase-specific timing in optimizing release velocity and overall performance. Targeted technical interventions focusing on these elements may help close the performance gap and advance elite-level outcomes.